Interobserver variation is a significant limitation in the diagnosis of Burkitt lymphoma - Rane, Swapnil Ulhas (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: The pathology of classic Burkitt lymphoma (BL) remains a challenge despite being a well-defined entity, in view of the significant overlap with atypical BL and B-cell lymphoma intermediate between DLBL (diffuse large B cell lymphoma) and BL. They are difficult to be segregated in resource-limited setups which lack molecular testing facilities. This is further affected by interobserver variability and experience of the reporting pathologist. AIMS: The aim of our study was to quantitate variability among a group of pathologists with an interest in lymphomas (albeit with variable levels of experience) and quantitate the benefit of joint discussions as a tool to increase accuracy and reduce interobserver variability of pathologists, in the diagnosis of BL in a resource-limited setup. MATERIALS AND METHODS: A set of 25 non-Hodgkin lymphoma cases in which a diagnosis of BL was entertained were circulated to 14 participating pathologist within the Mumbai lymphoma study group. A proforma recorded the morphologic and immunohistochemical features perceived during the initial independent diagnosis followed by a consensus meeting for discussion on morphology and additional information pertinent to the case. STATISTICAL ANALYSIS AND RESULTS: The concordance was poor for independent diagnosis among all the pathologists with kappa statistics (±SE) of 0.168 (±0.018). Expert lymphoma pathologists had the highest (albeit only fair) concordance (kappa = 0.373 ± 0.071) and general pathologists the lowest concordance (kappa = 0.138 ± 0.035). Concordance for morphological diagnosis was highest among expert lymphoma pathologists (kappa = 0.356 ± 0.127). Revision of diagnoses after consensus meeting was highest for B-cell lymphoma intermediate between DLB and BL. To conclude, interobserver variation is a significant problem in BL in the post WHO 2008 classification era. Experience with a larger number of cases and joint discussion exercises such as the one we conducted are needed as they represent a simple and effective way of improving diagnostic accuracy of pathologists working in a resource-limited setup.